Evaluasi Rasionalitas Penggunaan Obat Antihiperlipidemia di Puskesmas Jailolo - Siska Julita Gea; Meilani Jayanti; Dian Parwati (Yayasan Bina Lentera Insan, 2026)
Antihyperlipidemic drugs are a therapy used to lower blood lipid levels to prevent cardiovascular disease. This study aims to evaluate the rationality of antihyperlipidemic drug use at the Jailolo Community Health Center based on the parameters of appropriate indication, appropriate drug, appropriate patient, and appropriate dosage. This study used a descriptive method with a retrospective approach, analyzing 100 patient medical records from January to October 2025. The assessment was based on clinical guidelines and cardiovascular risk stratification. The results showed an indication accuracy of 99%, drug accuracy of 65%, patient accuracy of 100%, and dose accuracy of 99%. Based on these parameters, the use of antihyperlipidemic drugs at the Jailolo Community Health Center was categorized as rational in 65% of patients, while 35% of patients were irrational based on the parameters of appropriate indication, appropriate drug, appropriate patient, and appropriate dosage.